Water Conflicts in Sub-Saharan Africa - Peña-Ramos, José Antonio; José López-Bedmar, Rafael; Sastre, Francisco Javier; Martínez-Martínez, Adrián (Frontiers in Environmental Science, 2022)
Freshwater is a strategic natural resource in any region of the world, and this is especially true for the Sub-Saharan Africa region. Sub-Saharan Africa states, where water ecosystems are strategic resources, are oriented towards regional conflict rather than cooperation. However, its fossil fuels—principally, oil and natural gas—have constantly been exposed to scientific scrutiny. To compensate for the scarcity of scientific literature on the issue, the article analyses the role of the unequal distribution of freshwater that has been generating conflicts in Sub-Saharan Africa from the time of decolonization. Next, these conflicts are examined. Recommendations on the non-conflictual use of water are provided.